2021
DOI: 10.3390/ma14216629
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Switching Effect of Memory Device Based on All-Inorganic Cspbbri2 Perovskite

Abstract: In this study, the CsPbBrI2 perovskite film was prepared by the preparation of the sol-gel and the spin-coating method, and the cubic lattice was stabilized by introducing Br+ into the CsPbI3 film, which solved the problem of instability of the traditional perovskite phase. Based on the CsPbBrI2 perovskite film, the Ag/CsPbBrI2/ITO memory device with a resistance switching effect was prepared. The morphology and phase compositions of the film were analyzed by scanning electron microscope and X-ray diffraction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that as-deposited WO 3 films with lower crystallinity demonstrated a higher resistance ratio [41], while HfO 2 films deposited at higher substrate temperatures exhibited excellent bipolar resistive switching behavior attributed to their larger grain size and higher crystallinity [42]. Moreover, the uniformity and density of the CsPbBrI 2 surface play a role in achieving nonvolatile, reliable, reproducible, and long-term stable resistive switching [43]. Additionally, a decrease in the set/reset operating voltage was observed with a decrease in the thickness of the NiO nanodisk [44].…”
Section: I-v Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that as-deposited WO 3 films with lower crystallinity demonstrated a higher resistance ratio [41], while HfO 2 films deposited at higher substrate temperatures exhibited excellent bipolar resistive switching behavior attributed to their larger grain size and higher crystallinity [42]. Moreover, the uniformity and density of the CsPbBrI 2 surface play a role in achieving nonvolatile, reliable, reproducible, and long-term stable resistive switching [43]. Additionally, a decrease in the set/reset operating voltage was observed with a decrease in the thickness of the NiO nanodisk [44].…”
Section: I-v Characteristicsmentioning
confidence: 99%
“…Electronics 2023, 12, x FOR PEER REVIEW 13 of 19 and higher crystallinity [42]. Moreover, the uniformity and density of the CsPbBrI surface play a role in achieving non-volatile, reliable, reproducible, and long-term stable resistive switching [43]. Additionally, a decrease in the set/reset operating voltage was observed with a decrease in the thickness of the NiO nanodisk [44].…”
Section: Samplementioning
confidence: 99%
“…The Br − (1.96 Å) and Cl − (1.81 Å) both have a smaller radius than I − (2.2 Å), so some groups have added them into CsPbI 3 . The CsPbI 3 structural stability increased with the bigger t values [9,25,26,[45][46][47][48][49][50][51]. The SCN − ion, a kind of pseudohalide ion, has a smaller radius, which could also strengthen the crystallization behavior of the CsPbI 3 film, and promoted the PCE to 17.03% [52].…”
Section: Introductionmentioning
confidence: 99%